2022
DOI: 10.1038/s41586-022-04460-3
|View full text |Cite|
|
Sign up to set email alerts
|

T cell responses to SARS-CoV-2 spike cross-recognize Omicron

Abstract: The SARS-CoV-2 Omicron variant (B.1.1.529) has multiple spike protein mutations1,2 that contribute to viral escape from antibody neutralization3–6 and reduce vaccine protection from infection7,8. The extent to which other components of the adaptive response such as T cells may still target Omicron and contribute to protection from severe outcomes is unknown. Here we assessed the ability of T cells to react to Omicron spike protein in participants who were vaccinated with Ad26.CoV2.S or BNT162b2, or unvaccinate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

50
415
4
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 522 publications
(516 citation statements)
references
References 49 publications
50
415
4
2
Order By: Relevance
“…Although we did not evaluate cell-mediated immunity and immune memory, it has been reported that after natural infection, the T-cell-mediated responses are targeted across a larger variety of epitopes than the humoral response, and therefore, might be more durable to genetic changes in viral epitopes [ 13 ]. Moreover, studies showed that the majority of CD4+ and CD8+ T-cell response to the spike protein induced by vaccination or prior natural infection cross-recognized the Omicron variant, thereby likely contributing to protection against severe disease [ 14 , 15 ]. In addition, Omicron-infected patients had similar T-cell responses to ancestral spike, nucleocapsid, and membrane proteins to those found in patients hospitalized in previous waves [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we did not evaluate cell-mediated immunity and immune memory, it has been reported that after natural infection, the T-cell-mediated responses are targeted across a larger variety of epitopes than the humoral response, and therefore, might be more durable to genetic changes in viral epitopes [ 13 ]. Moreover, studies showed that the majority of CD4+ and CD8+ T-cell response to the spike protein induced by vaccination or prior natural infection cross-recognized the Omicron variant, thereby likely contributing to protection against severe disease [ 14 , 15 ]. In addition, Omicron-infected patients had similar T-cell responses to ancestral spike, nucleocapsid, and membrane proteins to those found in patients hospitalized in previous waves [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies showed that the majority of CD4+ and CD8+ T-cell response to the spike protein induced by vaccination or prior natural infection cross-recognized the Omicron variant, thereby likely contributing to protection against severe disease [ 14 , 15 ]. In addition, Omicron-infected patients had similar T-cell responses to ancestral spike, nucleocapsid, and membrane proteins to those found in patients hospitalized in previous waves [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of evasion of cell‐mediated immunity, available information suggests that this immunity induced by vaccines or previous infections remains effective against the Omicron variant. 73 , 74 , 75 However, some mutations, particularly in the ORFs may play a role in immune evasion of the Omicron variant. For example, deletions in ORF1a (L3674, S3675, and G3676) may enhance immune evasion by suppressing viral autophagy.…”
Section: Immune Evasion Of Sars‐cov‐2 Omicronmentioning
confidence: 99%
“…Despite the reduced neutralising activity of vaccinated individual sera against the Omicron variant, persistent protection against severe disease might be explained by the fact that vaccine-or infection-induced cellular immunity appears robust against the Omicron variant [79,80]. It is crucial to emphasize that vaccine effectiveness against symptomatic Omicron variant infection, and hospitalisation decreases over time, as stated by numerous studies [4,75].…”
Section: Impact Of Vaccines On Omicron Infectionmentioning
confidence: 99%